Symptoms of post- chimurenga war traumas : ex-combatants in post- independence Zimbabwean literature - Viriri, Advice (Midlands State University, 2014)
The paper establishes the prevalence of war traumas, related symptoms and prevention; and intervention strategies in all Zimbabwean communities where we have mad ex-combatants and the psychologically affected ones. It goes on to explore ways in which culture influences the perception of trauma in an African cultural context. What is conceived as traumatic experience differs from culture to culture. The selected body of Zimbabwean war literature namely: Shimmer Chinodya’s Harvest of Thorns (1989), Emmanuel Chiwome’s Masango Mavi (1998), Clemence Chihota & Robert Muponde’s No More Plastic Balls (2000), College Press’s A Roof to Repair (2000), Alexander Kanengoni’s Echoing Silences (1997) and Ignatius Mabasa’s Mapenzi (1999) sufficiently depicts the psychosocial magnitude of the effects of the Chimurenga War. The evidence presented in this paper from the selected war literature is an attempt to diagnose the impact of Chimurenga war and the psychoneurosis bedevilling Zimbabwe’s post-colonial mental environment, especially the ex-combatants. The war itself is given a nuanced investigation because the primary issue is on the most important forms of man-made violence where the magnitude of its effects manifests itself in the post-independence Zimbabwe. Very little research has been done regarding the colossal effects of the Chimurenga war. It is this paper’s major contribution to assess the psychosocial consequences of the conflict during this war and to find desirable culturally congruent local therapies to help excombatants cope with the illnesses. The present researcher is fully convinced that treating public illness has long been a process of trial and error guided by public attitudes and medical theory. This shapes and affects memories and institutions, rituals and daily practices that are related to present Zimbabwean political culture and hegemony. The researcher is heavily influenced by contemporary post-colonial, literary theories of psychoanalysis and other related theoretical protocols with niches in African war discourse.